Identification of Pathogenic Bacteria from Nile Tilapia Oreochromis niloticus in Freshwater of Sigi Regency, Central Sulawesi - Manurung, Usy Nora; Wijanarko, Wijanarko; Mauru, Serli; Manurung, Melani (Jurnal Natur Indonesia, 2024)
This research aims to identify the types of bacteria that infect tilapia (Oreocromis niloticus) cultivated in Sigi Regency and analyze air quality parameters (temperature and pH). This research was carried out from May to July 2023. Bacteria was isolated and identified at the Fish Quarantine Station Testing Laboratory, Quality Control and Safety of Fishery Products in Palu City. The target organ examined is the kidney. Bacteria were grown on TSA media and then isolated. On bacteria, Gram staining, motility, aerobic, catalase, oxidase, O/F, glucose, and Rimlershots media tests were carried out for Aeromonas hydrophila. Based on the test results, bacterial identification was done using the Manual to Identify Medical Bacteria. Of the 50 samples identified, 25 types of pathogenic bacteria were found that attack tilapia. In Sigi Biromaru District, there were seven types of bacteria Bordetella sp, Pseudomonas alcaligenes, Pasteurella sp, Moraxella sp, Shigella sp, Enterobacter sp, Achromobacter sp. In Dolo District, there were ten types of bacteria, namely Flavobacterium sp, Achromobacter sp., P.haemlytica, Alcaligenes sp, A.salmonicida, Actinobacillus sp, Plesiomonas shigelloides, A.sobria, Citrobacter sp, and Chromobacterium sp. In the Dolo Barat District, there are eight types of bacteria: P.shigelloides, Veillonella sp, Acinetobacter sp, Pasteurella sp, Plesiomonas sp, Bacillus sp, Enterococcus sp, and A.caviae. In Sigi Kota District, there are eight types of bacteria, namely Plesiomonas sp, P.haemlytica, P.alcaligenes, Klebsiella sp, Legionella sp, A.caviae, Eikenella corrodens, and Moraxella sp. In Marawola District, there are seven types of bacteria, namely P.haemlytica, E.corrodens, Klebsiella sp, Acinetobacter sp, Pasteurella sp, P.shigelloides, and Moraxella sp.